The Influence of Traditional Market Revitalization on Traders' Income (Case Study of Morning Market Traders in Samarinda City) - Salsabila Salsabila; Dini Zulfiani (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine whether or not there is an influence of morning market traders' income on the revitalization of the morning market in Samarinda City. This study uses a quantitative research type; the population in this study amounted to 40 morning market traders who have been relocated to several traditional markets and modern markets in Samarinda City. The sampling method used is the random sampling technique, the data collection technique used is a questionnaire and documentation, and the data analysis used is simple linear regression. The results of the study indicate that there is a moderate level of influence between the market revitalization variable and traders' income, the index results of which are at 0.40 - 0.599. This is evidenced by the correlation coefficient value of 0.584. Proof of the hypothesis with the t table value is obtained at a significance level of 5% of 1.685 from the t count value of 4.439. Because the t-count value is greater than the t-table value, H0 is rejected and Ha is accepted, meaning that market revitalization has a significant effect on traders' income. The conclusion in this study is that there is a significant influence of market revitalization and traders' income.